Pemanfaatan Laman Let’s Read Kategori Cerita Rakyat sebagai Media Pembelajaran Inovatif BIPA Keterampilan Membaca - Afrani, Aurora; Suyatno, Suyatno; Mulyono, Mulyono (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
The era of digitalization has caused learning activities to be increasingly integrated with technology. This is based on the many learning pages that can support learning objectives, one of which is the Let's Read page. This page can be used as a BIPA learning medium because the characteristics of the reading in it are appropriate to the level of knowledge of BIPA students. This research aims to analyze three forms of use of the Let's Read page in the folklore category as an innovative BIPA learning medium for reading skills. The three forms referred to are as a means of mastering vocabulary, a source of innovative reading, a means of introducing Indonesian culture and literature. The method used in this research is descriptive qualitative. This research data is in the form of sentences from interviews with BIPA students as well as the results of researchers' analysis of the Let's Read page. Data collection was carried out through interviews and observations. The research results show that the Let's Read page in the folklore category can be used as an innovative BIPA learning medium for reading skills.